Relationship between Anxiety and Other Personality Traits among Students in a Malaysian University - Asgari, Yasmin (2002)
This study was an attempt to investigate the relationship between anxiety and personality traits among students of Universiti Putra Malaysia. In addition, demographic factors associated to students' anxiety and personality traits were determined. The study hopes to provide more insight on mental health that could enhance the alleviation of social and academic problems among students and increase their academic achievement. The present study is a descriptive correlational research. The relationship of state and trait anxiety and personality traits was investigated. Besides, the differences in demographic variables with regards to anxiety and differences between personality traits of anxious and non-anxious students were also examined. Five faculties were randomly selected from the list of 13 faculties at Universiti Putra Malaysia. Accordingly, based on the knowledge disciplines, 263 subjects were selected from the five faculties using the cluster random sampling. Two instruments, EPQ and ST AI (form Y) were used in data collection to measure state and trait anxiety. The results indicated that in general, and in comparison with some other countries, students had moderate level of state and trait anxiety. All statistical analysis in this study showed the validity of Eysenck's theory (Eysenck, 1947, 1952) and Spielberger's model of anxiety (Spelberger, 1966), Introversion and Neuroticism were positively related to state and trait anxiety (P<.05) while Extraversion and Stability were negatively correlated to state and trait anxiety (P<.05). Moreover, significant differences were found in anxiety across some demographic variables including: age, gender, ethnicity, course of study, marital status and place of residence. Besides, significant relationship was reported between personality traits and some demographic variables. Finally, the stepwise multiple regression revealed that the personality traits and some demographic variables had significant linear relationship with anxiety.